Measurement of The Financial Acceptance for Project of Replacement RTG Engine to RTG Electric - Wibowo, Agung Aryo; Utomo, Christiono (Institut Teknologi Sepuluh Nopember, 2020)
Semarang Container Terminal, one of the container terminal operators, wants to prevent growth container throughput with maintaining container loading and unloading services efficiently. Nowadays, technological development can support for the management of loading and unloading activities. Modern technology has created sophisticated equipment to increase port productivity. One of the modern equipments is Automated Rubber Tyred Gantry (ARTG) which uses electricity without an operator cabin. It can be potential savings at operational costs, the fuel/material costs, maintenance costs, and human resource costs. Therefore, Semarang Container Terminal has plan to replace their old RTG (Rubber Tyred Gantry) to ARTG, but the project investment still need to be analyzed for presenting the financial firm impact. This study has analyzed using incremental analysis method compared each alternative. The results presented that ARTG investment was the best alternative. To find out how sensitive the investment parameters influenced a decision, must been analyzed using sensitivity analysis. The final conclusion from this study showed the project of replacement RTG engine to ARTG had been effected by the increased procurement cost by 20% and the added 9% from existing tarif